Development of solar water pump for small scale paddy field irrigation - Noor Syafawati Ahmad (School of Electrical Systems, University Malaysia Perlis, 2010)
In this thesis, the solar powered water pump have been thoroughly investigated and analyzed in terms of the Photovoltaic (PV) module electrical output, performance, field observation, and modeling of solar radiation. The objective of this research is to obtain the solar radiation using Hargreaves method, determine the PV electrical output through some installation and specification required to apply for paddy fields irrigation.